SEX - RATIO OF LIBYAN POPULATION - J. Dutta, J. Dutta; A. Sharif, A. Sharif (Dirasat in Economics and Business, 1968)
One of the most important characteristics of the population of a country is its sex composition. The replacement and growth of a population is largely dependent on the proportion of females in the population.